Lung Cancer-Specific Mortality Risk and Public Health Insurance: A Prospective Cohort Study in Chongqing, Southwest China - Wang, Yuqi; Lei, Haike; Li, Xiaosheng; Zhou, Wei; Wang, Guixue; Sun, Anlong; Wang, Ying; Wu, Yongzhong; Peng, Bin (Frontiers in Public Health, 2022)
Objective The incidence and mortality of lung cancer rank first among malignant tumors, and its long treatment cycle will bring serious economic burdens to lung cancer patients and their families. There are few studies on the prognosis of lung cancer and insurance policies. This article explores the relationship between the lung cancer-specific death and public health insurance, self-paying rate, and the joint effect of public health insurance and self-paying rate. Materials and Methods A prospective longitudinal cohort study was conducted in Chongqing, China from 2013 to 2019. The chi-square test was used to describe the emographic and clinical characteristics of patients with different insurance types and different self-paying rates. Multivariate logistic regression was used to analyze the relationship between patients with different insurance types, self-paying rates, and lung cancer treatment methods. Finally, the Cox proportional hazard model and the competitive risk model are used to calculate the cumulative hazard ratio of all-cause death and lung cancer-specific death for different insurance types and different self-paying rate groups. Results A total of 12,464 patients with lung cancer were included in this study. During the follow-up period (median 13 months, interquartile range 5.6-25.2 months), 5,803 deaths were observed, of which 3,781 died of lung cancer. Compared with patients who received urban resident-based basic medical insurance , patients who received urban employee-based basic medical insurance had a 38.1% higher risk of lung cancer-specific death (HRs)=1.381, 95% CI: 1.293-1.476, P<0.005), Compared with patients with insufficient self-paying rate, patients with a higher self-paying rate had a 40.2% lower risk of lung cancer-specific death (HRs= 0.598, 95% CI: 0.557-0.643, P<0.005). Every 10% increase in self-paying rate of URBMI reduces the risk of lung cancer-specific death by 17.6%, while every 10% increase in self-paying rate of UEBMI reduces the risk of lung cancer-specific death by 18.0%. Conclusions The self-paying rate for lung cancer patients is relatively high, and the National Medical Insurance Administration should increase the reimbursement rate for lung cancer-related diseases. On the other hand, high-risk groups should increase their awareness of early lung cancer screening.